Condition of the surface zooplankton in the eastern part of the Black Sea during the autumn of 1996. - Musaeva, Eteri I; Gagarin, Vladimir I (PANGAEA, 2000)
On the basis of analyses of samples collected in the eastern Black Sea in September 1996 trends of increase in surface zooplankton biomass and general decrease in Mnemiopsis biomass were revealed.
(Table 2) Abundance and biomass of zooplankton in the eastern Black Sea in the beginning of September 1996
Keywords: Archive of Ocean Data; ARCOD; Aurelia; Aurelia, biomass; Aurelia, biomass, as energy; Binocular microscope; Black Sea; DEPTH, water; Mnemiopsis; Mnemiopsis, biomass; Mnemiopsis, biomass, as energy; Plankton net BR 113/140; PLANKTY program of biomass calculation from measured data; PN-BR; YuMG-96-10; YuMG-96-17; YuMG-96-19; YuMG-96-19a; YuMG-96-23; YuMG-96-24; YuMG-96-25; YuMG-96-26; YuMG-96-33; YuMG-96-34; YuMG-96-35; YuMG-96-36; YuMG-96-37; YuMG-96-44; YuMG-96-45; Zooplankton; Zooplankton, biomass; Zooplankton, biomass, as energy